Principal’s Facial Expression, Organization Citizenship Behaviour and Performance of Secondary Schools in Nairobi - Mute, Godfrey Ngunyi; K’Obonyo, Peter; Ogutu, Martine; Njihia, James (American Journal of Education and Learning, 2020)
There is no literature in Africa that shows the relationship of leader’s facial expression, organization citizenship behavior and performance in learning institution. However each variable is said to affect performance. This study closed the gap by establishing the moderating effect of organization citizenship behavior on the relationship between principal facial expression and secondary school performance in public secondary schools in Nairobi City County. The hypothesis stated that Organization citizenship behavior moderates the relationship between principal’s facial expression and performance of secondary schools in Nairobi City County. Research method was a survey method involving positivist’s research philosophy, descriptive and cross section research design. A census sampling method was used. 55 secondary schools were considered and 278 teachers were used to respond to the questions. Step by step data analysis method was used. The study finding showed that the moderating effect of organization citizenship behaviour in the relationship between Principal facial expression and Secondary school performance in Nairobi City County was not significant. Conclusion from the study stated that organization citizenship behaviour and Principal’s facial expression are independent of each other and affect performance of public secondary schools in Nairobi not in any relationship. It was recommended that each variable should be tested its effect on secondary schools’ performance differently.